From decidualization to pregnancy progression: An overview of immune and metabolic effects of VIP - Ramhorst, Rosanna Elizabeth (2022)
Background: A tight immune and metabolic regulation underlies the early maternal-placental interaction to assist the energetic dynamic demands of the fetus throughout pregnancy. The vasoactive intestinal peptide (VIP) holds biochemical, metabolic and immune properties consistent with a regulatory role during pregnancy. Aim: Here we overview critical aspects of embryo implantation and placental development with special focus on the immune and metabolic effects of VIP expressed by decidual and trophoblast cells. Content: During decidualization, endometrial stromal cells undergo reticular stress and trigger unfolded protein response (UPR) that enable expansion of their endoplasmic reticulum and immunomodulatory factor synthesis. These processes appear differentially affected in recurrent abortion and in vitro fertilization failure suggesting their relevance in reproductive pathologies. Similarly, defective placentation associates with altered immune, vascular and trophoblast interaction resulting in complicated pregnancies that threaten maternal and neonatal health and underlie metabolic programming of adult life. We discuss the most recent research on decidual, trophoblast and immune cell interaction on the light of VIP regulation. Its role in decidualization and UPR associated with a sterile inflammatory response and angiogenesis is discussed. Evidence on VIP modulation of cytotrophoblast cell function, metabolism and immune profile is revised as well as the shaping of decidual leukocyte phenotype and function from decidualization to term. Implications: The broad spectrum of effects of VIP from implantation to term in normal and pathological conditions summarized here might contribute to the identification of novel biomarkers for diagnosis and pharmacological targeting.